2003
DOI: 10.1111/1475-4754.00094
|View full text |Cite
|
Sign up to set email alerts
|

Strontium Isotopes in the Investigation of Early Glass Production: Byzantine and Early Islamic Glass from the Near East*

Abstract: 87Sr/ 86 Sr ratios have been determined for glasses from four production sites, dated to between the sixth and the 11th centuries, in the Eastern Mediterranean region. On the basis of elemental analyses, the glasses at each location are believed to have been melted from different raw materials. Two glass groups, from Bet Eli'ezer and Bet She'an, in Israel, are believed to have been based upon mixtures of Levantine coastal sands and natron, and have 87 Sr/ 86 Sr ratios close to 0.7090, plus high elemental stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
206
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(235 citation statements)
references
References 28 publications
(38 reference statements)
21
206
0
1
Order By: Relevance
“…Glasses fluxed with mineral soda typically contain potash and magnesia at concentrations less than 1.5 % [17]. It is of interest that two Compositional data are presented for each sample as average oxide weight percent data for replicate analyses (first row), and one standard deviation for the replicate analyses TS = Type series.…”
Section: General Characteristicsmentioning
confidence: 99%
“…Glasses fluxed with mineral soda typically contain potash and magnesia at concentrations less than 1.5 % [17]. It is of interest that two Compositional data are presented for each sample as average oxide weight percent data for replicate analyses (first row), and one standard deviation for the replicate analyses TS = Type series.…”
Section: General Characteristicsmentioning
confidence: 99%
“…Recent studies have demonstrated the great potential of isotopic analysis for glass provenance study in the case of Roman, Late Antique and Byzantine glass [22,[37][38][39][40].…”
Section: Isotopic Analysismentioning
confidence: 99%
“…Therefore, something more than just the bulk chemical data of the glasses is needed to enable successful provenancing. Several attempts have been made to use a variety of techniques to provenance glass, these include trace element analysis, rare earth element patterns and isotopic signatures Degryse and Shortland, 2009;Freestone et al, 2003;Henderson et al, 2005;Shortland et al, 2007;Wedepohl and Baumann, 2000). In particular, Sr-Nd isotopic signatures have been used to indicate that the majority of the Roman glass found in Europe came from the Eastern Mediterranean region (Freestone et al, n.d.).…”
Section: Glass Provenancingmentioning
confidence: 99%